Behaviour of the radiation of the suprathermal electrons at the Uragan-3M torsatron after RF heating off from ECE measurements - Zamanov, N.V.; Pavlichenko, R.O.; Kulaga, A.E.; Grigo’eva, L.I.; Chechkin, V.V.; Shapoval, A.N.; Makhov, M.M.; Mironov, Yu.K.; Romanov, V.S.; Tarasov, I.K.; Sitnikov, D.A.; Pavlichenko, O.S. (Вопросы атомной науки и техники, 2015)
The microwave radiometry is a well-known diagnostics to obtain the information on temporal evolution and radial profile of the electron temperature at U-3M torsatron plasma experiments. However, under low plasma density with this diagnostics we report on the large production of runaway electrons after RF heating pulse off. We notice a gradually increasing of the radiometer signal at the frequencies that match the second and third harmonics of electron cyclotron emission of the extraordinary mode. This effect could be explained with the existence of the “runaway” electrons in U-3M discharge. A phenomenological description of this process is presented, where the time evolution of the ECE radiation signal is compared to the electron density evolution.